The impact of CEO background characteristics on corporate innovation and firm performance in China - Zhang, Meinian (2022)
As the top managers in the formulation and execution of corporate strategic decisions, the background characteristics of CEOs shape their individual mindsets and decision-making preferences, and consequently influence the strategic options and implementation of the company. Relying on upper echelons theory, this study aims to examine the role of background characteristics of CEOs on corporate innovation and performance. While the majority of existing studies are based on superficial CEO demographic characteristics, this research selects CEO academic, technical and overseas background characteristics, which are relatively less commonly addressed at present, and deepens the analysis and compares the intensity of the role of different types of CEOs on corporate innovation and performance. Secondary data was collected and collated from the CSMAR database to establish a sample database of Chinese listed companies from 2013 to 2017. Detailed research hypotheses and regression models are constructed step-by-step incrementally in line with the research framework. This study applies STATA statistical analysis software and multiple regression analysis methods for empirical testing. Secondary data was collected and collated from the CSMAR database to establish a sample database of Chinese listed companies from 2013 to 2017. Detailed research hypotheses and regression models are constructed step-by-step incrementally in line with the research framework. This study applies STATA statistical analysis software and multiple regression analysis methods for empirical testing. The results of the study show that CEO academic background characteristic plays a positive role in both innovation and performance. The technical background of the CEO has a more significant effect on corporate innovation than the academic background, but has no significant effect on corporate performance. There is no significant effect of overseas background on both innovation and performance. The empirical outcomes provide a data reference for firms in formulating criteria for selecting CEOs. It also illustrates that the capability and efficiency of different types of CEOs in achieving enterprise innovation and revenue are varied, offering a realistic basis for research on innovation and performance. In addition, this article suggests that innovation inputs could be introduced for in-depth study in future research and also investigate whether there is a mediating role for corporate innovation in the relationship between CEO background characteristics and corporate performance.